Financial conditions, local competition, and loca market leaders: The case of real estate developers - Ying Fan; Charles Ka Yui Leung; Zan Yang (Osaka University, Institute of Social and Economic Research (ISER), 2021)
This paper studies whether (and how) corporate decisions are affected by internal factors (such as the financial conditions of own company) and external factors (such as the actions of local competitors) in an imperfectly competitive environment. We study the listed real estate developers in Beijing as a case study. Our hand-collected dataset includes transaction-level information booked indicators (such as profitability, liability, and liquidity) and un-booked financial indicators (political connections). Our multi-step empirical model shows that both the firm's financial conditions and her competitors' counterparts are essential but play different roles in the output design, pricing, and the time-on-the-market (TOM). Internal versus external factors' relative importance relates to the degrees of market concentration in a nonlinear manner. Local market leaders' existence alters the small firms' strategy and leads to higher selling prices and slower selling pace in the local market. Our findings survive various robust checks.
Keywords: G11; R30; L10; 330; corporate financial status; output market decision; internal and external driven; realestate developers; housing supply